Baiq Nuril Case and Discourse on Freedom of Expression - Akhmad, Muhammad Zaidan Syafiqy; Arifin, Ridwan (Faculty of Law, Universitas Negeri Semarang, 2022)
Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) was originally born as a legal product in response to the advancement of information and communication technology developments in the world which have significantly changed the pattern of people's lives in multi-sectors of human life. The purpose of the establishment of the ITE Law is to guarantee the rights of the community and maintain the stability of the internet flow from things that can damage it. However, in fact there are still many defects contained in the content of the a quo Law which is multi-interpretable and can be misused by certain parties. Baiq Nuril is an honorary teacher who was sexually harassed by his superiors, but was found guilty by the Supreme Court and charged with Article 27 paragraph (1) in conjunction with Article 45 paragraph (1) of the ITE Law. From the point of view of victim protection, victim protection also contributes to the realm of criminal law, especially regarding criminal matters and punishment for the creation of a law. Victimology is an applied science that makes criminal and criminal charges against perpetrators more equal and accountable. With the clarity of the position and role of the victim in the occurrence of a crime, it can be used as one of the considerations for judges as decision makers to decide the type and amount of criminal punishment that will be assigned to the perpetrator as victim protection. Through this simple article, the author will provide an explanation and understanding of the case experienced by Baiq Nuril in Indonesian criminal law in terms of victimology perspective through normative juridical research methods of library law research, as well as data collection through library research methods.